Industrializacja ziem polskich w historiografii a problem udziału ziemiaństwa w tym procesie w XIX i na początku XX w. - Puś, Wiesław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The researches on the history of industry in Poland last from the end of 19th century. The biggest number of publications appeared after the Second World War. The works from historical centres in Warsaw, Łódź, Poznań, Cracow, Wrocław and Katowice deserve special attention. Unfortunately the large achievement of Polish historians lack publications about participation of landed gentry in the industrialization of the Polish territories.